Review of Teaching the Way: Using the Principles of The Art of War to Teach Composition by Steven T. Nelson - Christian Smith (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
First, an admission, or perhaps a confession: my enthusiasm for teaching composition has been waning in the last year or two. I don’t know if it was the pandemic coupled with the resulting year on Zoom or the cumulative effect of teaching writing for the last decade and a half, but somewhere along the way it became a different experience. All too often after grading or having a lesson plan fall flat, I would repeat the first two lines from Geoffrey Sirc’s underappreciated review article, “Resisting Entropy,” when he says “Teaching writing is impossible. You have ten to fifteen weeks to do … what?”
Keywords: JAEPL